Isolation of Plant Growth Promoting Rhizobacteria (PGPR) from different type of organic material and comparison of paddy growth rate at vegetative phase using isolated PGPR / Mohamad Syafiqul Hafiz Mohamad Faisal - Mohamad Faisal, Mohamad Syafiqul Hafiz (Faculty of Plantation and Agrotechnology, 2019)
Organic material such as cow dung, goat dung, fish dung and chicken dung are largely use in almost every farm because of organic material gives a high benefits to the soil and it is also good for the ecosystem, but each of the organic material does not contain high amount beneficial microorganism that can give benefits to the farm soil, each type of bacteria have their own mechanism on how to serve the ecosystem, for example, Actinomycete, Pseudomonas, Bacillus bacteria that use for promoting plant growth. This research was conducted to isolate the beneficial microorganism on each organic material and application on the early phase of vegetation seed of paddy (Oryza sativa). The research activities and data analysis was conducted in UiTM (Melaka) Jasin Campus Kampung Seri Mendapat. This research was carried out near 4 month starting from August until November 2018. Lab research show that, 4 bacteria that positive on the NBRIP from 27 bacteria that gain from 4 difference sample. The experimental design was Completely Randomized Design (CRD) with 4 treatment and 3 replication. Treatment 1(Control), Treatment 2(Fish dung bacteria), Treatment 3(Cow dung bacteria) and treatment 4(Goat dung bacteria). This study show that by using T-test, treatment 2 showed a significant different in number of tiller compare to control while treatment 3 and 4 show insignificant. The height of paddy does not show significant difference compare to control.